2003
DOI: 10.1002/art.10864
|View full text |Cite
|
Sign up to set email alerts
|

A poly(ADP‐ribose) polymerase haplotype spanning the promoter region confers susceptibility to rheumatoid arthritis

Abstract: Objective. To investigate the association of the poly(ADP-ribose) polymerase 1 (PARP-1) gene promoter polymorphism with rheumatoid arthritis (RA) predisposition.Methods. An association study with 213 Spanish RA patients and 242 healthy subjects was carried out to investigate the association of all known PARP-1 gene promoter polymorphisms, i.e., a CA microsatellite repeat, a poly(A) n , and 3 single point mutations (C410T, C1362T, and G1672A), with disease susceptibility. Additionally, we analyzed the distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 15 publications
3
49
1
Order By: Relevance
“…In addition to the beneficial effects of PARP inhibitors and protection provided by knockout phenotypes, the role of PARPs in inflammation is also indicated by association of certain PARP-1 promoter haplotypes and SNPs with diseases. Such associations have been reported for systemic lupus erythematosus [76], autoimmune nephritis [76] or rheumathois arthritis [77] further supporting a possible link between PARP-1 and autoimmune inflammation.…”
Section: Inflammatory Diseases Mediated By Poly(adp-ribose) Polymerasessupporting
confidence: 58%
“…In addition to the beneficial effects of PARP inhibitors and protection provided by knockout phenotypes, the role of PARPs in inflammation is also indicated by association of certain PARP-1 promoter haplotypes and SNPs with diseases. Such associations have been reported for systemic lupus erythematosus [76], autoimmune nephritis [76] or rheumathois arthritis [77] further supporting a possible link between PARP-1 and autoimmune inflammation.…”
Section: Inflammatory Diseases Mediated By Poly(adp-ribose) Polymerasessupporting
confidence: 58%
“…The length of the CA microsatellite in the promoter has not only been implicated in transcription of PARP-1 but has also been (Pascual et al, 2003). Previous studies showed that a long CA microsatellite is related to autoimmune diseases, namely, rheumatoid arthritis and coeliac disease (Pascual et al, 2003;Rueda et al, 2005). This evidence implicates PARP-1 primarily in inflammatory processes leading to the development of immunological disorders, but these may also lead to promotion and development of cancer by NF-kB dependent or independent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, due to the small sample number, we did not find any significant correlation between PARP-1 activity and T2444C genotype ( Figure 2C). The length of the CA microsatellite in the promoter has not only been implicated in transcription of PARP-1 but has also been (Pascual et al, 2003). Previous studies showed that a long CA microsatellite is related to autoimmune diseases, namely, rheumatoid arthritis and coeliac disease (Pascual et al, 2003;Rueda et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic variants within this region may therefore affect PARP-1 expression and inducibility. In this context, it is puzzling that specific haplotypes of parp-1 promoter confer higher risk of autoimmune disorders such as rheumatoid arthritis (56), celiac disease (57), and systemic lupus erythematosus (58). It is therefore tempting to speculate that induction of PARP-1 in DCs and/or other immune cells participates in development of autoimmunity.…”
Section: Discussionmentioning
confidence: 99%